Tingkat Pengetahuan Remaja Di Kelurahan Mangunsuman Kecamatan Siman Kabupaten Ponorogo Terhadap Perbankan Syariah - Indriana Muchtarotul Azizah; Said Abadi (Institut Agama Islam Negeri Ponorogo, 2022)
Knowledge is all the results of activities on a certain object and makes a broader view that can change the attitude of individuals and groups. The influencing factors are experience, information, socio-culture, environment, education and age. Mangunsuman Village is a strategic area close to the Islamic University and Sharia Bank ATM Facilities. However, from initial observations in the field, Mangunsuman teenagers do not really understand Islamic banking. So that further research is needed. The purpose of this study was to determine the level of knowledge of adolescents about Islamic Banking in Mangunsuman Village and the factors that influence adolescent knowledge of Islamic Banking in Mangunsuman Village. The method used is qualitative with a case study approach. Collecting data using a questionnaire to 62 respondents, interviews with 7 informants and observations. The data collection technique in this study used a non-probability sampling technique with the type of snowball sampling. The results of this study indicate that the knowledge level of Mangunsuman teenagers in Islamic banking is quite good but still in the low category. However, it is still low because they do not understand the operational system of Islamic banks, the difference between Islamic banks and commercial banks, the supervisory board and interest in using Islamic bank products is still low. The lack of information and interaction between Islamic banks and teenagers causes a lack of confidence and trust in using Islamic bank products. Factors that influence knowledge of Islamic banking in Mangunsuman adolescents include education, information/mass media, socio-economic culture, environment, experience, and age. Pengetahuan adalah semua hasil kegiatan pada suatu objek tertentu dan menjadikan pandangan yang lebih luas yang dapat mengubah sikap individu dan kelompok. Faktor yang mempengaruhi adalah pengalaman, informasi, sosial budaya, lingkungan, pendidikan dan usia. Desa Mangunsuman merupakan kawasan strategis dekat dengan Universitas Islam dan Fasilitas ATM Bank Syariah. Namun dari pengamatan awal di lapangan, remaja Mangunsuman belum begitu memahami perbankan syariah. Sehingga diperlukan penelitian lebih lanjut. Tujuan penelitian ini adalah untuk mengetahui tingkat pengetahuan remaja tentang Perbankan Syariah di Desa Mangunsuman dan faktor-faktor yang mempengaruhi pengetahuan remaja tentang Perbankan Syariah di Desa Mangunsuman. Metode yang digunakan adalah kualitatif dengan pendekatan studi kasus. Pengumpulan data menggunakan kuesioner kepada 62 responden, wawancara dengan 7 informan dan observasi. Teknik pengumpulan data dalam penelitian ini menggunakan teknik non-probability sampling dengan tipe snowball sampling. Hasil penelitian ini menunjukkan bahwa tingkat pengetahuan remaja Mangunsuman dalam perbankan syariah cukup baik namun masih dalam kategori rendah. Namun masih rendah karena belum memahami sistem operasional bank syariah, perbedaan antara bank syariah dan bank umum, dewan pengawas dan minat menggunakan produk bank syariah masih rendah. Minimnya informasi dan interaksi antara bank syariah dengan remaja menyebabkan kurangnya keyakinan dan kepercayaan dalam menggunakan produk bank syariah. Faktor-faktor yang mempengaruhi pengetahuan perbankan syariah pada remaja Mangunsuman antara lain pendidikan, informasi/media massa, sosial ekonomi budaya, lingkungan, pengalaman, dan usia.